Green fertilizer at planting time - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Robin Mlolo, a farmer from Malawi?s lakeshore area, describes the many benefits to be gained from Faidherbia albida, the African winterthorn.